Bring Back the Noise: How Cariou v. Prince Will Revitalize Sampling - Azran, Julian (The Columbia Journal of Law & the Arts, 2015)
In 1988, John Carlin argued in an article in this Journal that fair use should be extended to cover works of appropriation art so as to protect appropriative artists from claims of copyright infringement. He wrote that “[a]n extension of fair use to cover artistic use through Appropriation would not compromise either the underlying logic of copyright law, or the intent of Congress in creating a legislative exception to copyright monopoly in the fair use doctrine.” In 1992, artist Jeff Koons unsuccessfully argued that one of his sculptures, which borrowed heavily from a photograph he purchased in a card shop, was fair use. But in 1994, the Supreme Court ruled that works of appropriation art do not inherently infringe on the original author’s copyright. Since then, courts have moved towards embracing Carlin’s view that copyright should encourage appropriation art by accepting such art as fair use, not condemn it by finding such art to be infringement. The most recent development came from the Second Circuit in Cariou v. Prince, where the court of appeals embraced perhaps the most expansive interpretation of fair use of any court yet. Up to this point, however, these cases have only involved visual art. This Note seeks to track the progress that courts have made towards accepting appropriation art as fair use and argues that the reasoning from recent cases dealing with visual art can also be applied to music.